2013
DOI: 10.1016/s1995-7645(13)60113-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Haoqinqingdan decoction on damp-heat syndrome in rats with influenza viral pneumonia

Abstract: Compared with ribavirin, the high dose Haoqinqingdan decoction can improve the ratio of T lymphocyte subgroup and Th1/Th2 cell balance more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Shengjiang Power can increase the percentage of CD8+ in peripheral blood, regulate the radio of CD4+/CD8+, and improve the immune function of the body (p<0.05 or p<0.01) (Nan et al, 2016b). Other study results have shown that compared with ribavirin, the Haoqin Qingdan Decoction can improve the ratio of T lymphocyte subgroup and Th1/Th2 cell balance more effectively in rats with damp-heat syndrome of influenza viral pneumonia (Zhang et al, 2013).…”
Section: Regulation Of Lymphocyte Subsetsmentioning
confidence: 96%
“…Shengjiang Power can increase the percentage of CD8+ in peripheral blood, regulate the radio of CD4+/CD8+, and improve the immune function of the body (p<0.05 or p<0.01) (Nan et al, 2016b). Other study results have shown that compared with ribavirin, the Haoqin Qingdan Decoction can improve the ratio of T lymphocyte subgroup and Th1/Th2 cell balance more effectively in rats with damp-heat syndrome of influenza viral pneumonia (Zhang et al, 2013).…”
Section: Regulation Of Lymphocyte Subsetsmentioning
confidence: 96%
“…For example, multiple ingredients from Chinese herbs counteract chemotherapy-induced gastrointestinal toxicity and kansui-induced hepatocyte cytotoxicity [ 10 , 11 ]. Haoqin Qingdan decoction (HQQD), a traditional Chinese formula widely used for the treatment of different diseases [ 12 , 13 ], consists of herbal materials of Artemisinin , bamboo shavings, Pinellia ternata , Indian buead , Scutellaria baicalensis , Aurantii fructus , Aurantii nobilis pericarpium , and Biyu powder. Although there are a lot of researches regarding HQQD, few of them are involved in the hepatotoxicity induced by CP.…”
Section: Introductionmentioning
confidence: 99%
“…HQD was generated as described by Zhang, et al (5) The main components in HQD were as follows: Artemisia carvifolia 10 g, Pinellia ternata Breit 10 g, Citrus aurantium L. 10 g, Caulis Bambusae in Taeniam 10 g, Scutellaria baicalensis 15 g, Isatis indigotica Fortune 15 g, Isatis tinctoria 15 g, Glycyrrhiza uralensis Fisch. 6 g, Citrus reticulata Blanco.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…inducing factor in FDDHS. (5) The toll-like receptor (TLR) 2 and nuclear factor (NF)-κB expression decreased in DHS mice during HQD therapy. (7) We hypothesized that innate immunity might mediate the progression and treatment of DHS.…”
mentioning
confidence: 99%